2021
DOI: 10.1111/tra.12779
|View full text |Cite
|
Sign up to set email alerts
|

Formation of retromer transport carriers is disrupted by the Parkinson disease‐linked Vps35D620Nvariant

Abstract: Retromer core complex is an endosomal scaffold that plays a critical role in orchestrating protein trafficking within the endosomal system. Here we characterized the effect of the Parkinson's disease‐linked Vps35 D620N in the endo‐lysosomal system using Vps35 D620N rescue cell models. Vps35 D620N fully rescues the lysosomal and autophagy defects caused by retromer knock‐out. Analogous to Vps35 knock out cells, the endosome‐to‐trans‐Golgi network transport of cation‐independent mannose 6‐phosphate receptor (CI‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 75 publications
4
36
0
Order By: Relevance
“…Our live cell imaging revealed that retromer endosomes labeled by Vps35D620N were less dynamic than those labeled by wildtype Vps35 and detected less frequently small, motile, Tetherin-containing vesicles in cells expressing mutant Vps35 with D620N than in cells expressing wildtype Vps35. These observations are consistent with recent findings showing that Vps35D620N impairs the production of transport carriers [21].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our live cell imaging revealed that retromer endosomes labeled by Vps35D620N were less dynamic than those labeled by wildtype Vps35 and detected less frequently small, motile, Tetherin-containing vesicles in cells expressing mutant Vps35 with D620N than in cells expressing wildtype Vps35. These observations are consistent with recent findings showing that Vps35D620N impairs the production of transport carriers [21].…”
Section: Discussionsupporting
confidence: 94%
“…The D620N mutation in Vps35 does not affect the formation of the Vps26/Vps35/Vps29 heterodimer nor alter cargo recognition [17]. Ectopically expressed as well as endogenous Vps35 with the D620N mutation induces the enlargement of retromer-positive endosomes and impairs the formation of retromer transport carriers and retrieval of dopamine D1 receptors, dopamine transporters, and many other proteins, including those involved in the degradation of α-synuclein [17][18][19][20][21]. The presence of D620N in Vps35 also impairs autophagy and causes accumulation of PD-variant α-synuclein A53T [22].…”
Section: Introductionmentioning
confidence: 99%
“…1A.i-ii; 1-way ANOVA p = 0.44). In cell lines, the D620N mutation impairs VPS35 association with the Wiskott-Aldrich syndrome protein and SCAR homolog (WASH) complex member family with sequence similarity 21 (FAM21) by coIP (44,45,47). We found the level of FAM21 pulled by VPS35 was similarly reduced in coIP of whole-brain lysates from mutant mice (Fig.…”
Section: Altered Protein Binding Relationships and Lrrk2 Kinase Activity In Vki Brainmentioning
confidence: 76%
“…Previous reports of VPS35 neurobiology at glutamatergic synapses, and the effects of the D620N mutant, have relied on exogenous protein expression or knock-out, and produced somewhat con icting results. Studies on retrograde tra cking of the canonical retromer cargo cation-independent mannose-6phosphate receptor (CI-MPR), for example, concluded that the mutation results in a loss-of-function (15,44,46,47) or has no effect (45,70). This discordance may result from the variety of cell types and modes of expression used to glean insights.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports of VPS35 neurobiology at glutamatergic synapses, and the effects of the D620N mutant, have relied on exogenous protein expression or knock-out, and produced somewhat conflicting results. Studies on retrograde trafficking of the canonical retromer cargo cation-independent mannose-6-phosphate receptor (CI-MPR), for example, concluded that the mutation results in a loss-of-function (15,44,46,47) or has no effect (45,70). This discordance may result from the variety of cell types and modes of expression used to glean insights.…”
Section: Discussionmentioning
confidence: 99%